Specification and design of component-based coordination systems by integrating coordination patterns. - Pérez-Serrano, Pedro L. (Software engineering notes.)
Rewriting logic has been revealed as a powerful tool to represent concurrent and state-transitions aspects in a declarative way, providing an adequate environment to specify and execute system representations. Moreover, rewriting logic is reflective, allowing for the definition of operations that transform, combine and manipulate specification modules by making use of the logic itself. Taking advantage of these capabilities, this paper presents a set of tools based on the rewriting logic language Maude to express the specifications of component-based systems with important coordination constraints, where coordination aspects are treated as separate components from functional ones. This representation allows for the testing of the system behavior from the early stages in the development process by executing the specifications. In addition, the development of basic coordination patterns using UML is presented to describe the coordination relationships between components in any system, providing a standard notation that complements the tools of the proposal.